(3eYGfj GdbQBf (B/s - (3GdaQGA, jMji Hf RjGO Hf YHO Gddg,s 144-207 (3g`(B.s; (3fLGJj, CMeO jhSas; (3GdfLGQ, eMeO Ydj,s 1895-1965; (3TdHj, YHO GdaJGM ESeGYjds ((3GdbGgQI (B:s (3OGQ GdcJH hGdhKGFb GdbhejI,s, 2013)
(3jJfGhd eYGfj GdbQBf GdcQje(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdbQBfs -- (3JaGSjQ dZhjIs; (3GdbQBfs -- (3CdaGXs